Onthe Singular Sturm-Liouville Problems that Have the Same Spectrum - Gulsen, Tuba; Ulusoy, Ismail (Amer Inst Physics, 2016)
The problem of efficaciously constucting the potential q (x) and the numbers h and H was solved in [1]. Trubowitz [2] investigated the isospectrality problem which have the same spectrum with other same type of problems. Then Jodeit and Levitan [3] considered this problem with a different approach, based on transmutation operators and integral equation. In this work, we discussed this problem for singular Sturm-liouville operator and obtained some important formulas for the number H, the potential q (x) and the norming constants alpha(n) .
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE
Keywords: Singular Sturm-Liouville Equation; Gelfand-Levitan Integral Equation; Kernel; Spectrum